Dissertation Proposal Guidebook : How to Prepare a Research Proposal and Get It Accepted. - Gardner, David (Charles C Thomas Publisher, LTD, 1980)
By David C. Gardner, Boston University, Boston, Massachusetts, and Grace Joely Beatty, American Training and Research Associates, Inc., Methuen, Massachusetts. This no-nonsense manual of dissertation proposal writing has been tested and refined in workshops for doctoral and master's candidates. It begins with a step-by-step approach to the selection of a manageable topic. This section contains examples of good and bad research topics and a lucid explanation of directional, non-directional and null hypotheses. Eighteen examples of key proposal elements, taken from proposals and dissertations th.